Analisis Dan Perancangan Sistem Informasi Geografis Pemetaan Daerah Rawan Bencana Banjir Pada Dinas Sosial Kota Jambi - Yulita, Fitri; Kurniabudi; Nurhadi (LPPM Universitas Dinamika Bangsa, 2024)
Abstract− The use of Geographic Information Systems (GIS) is crucial for mapping flood-prone areas, especially in Jambi City, which frequently experiences flooding due to high rainfall. GIS helps identify high-risk areas, speeds up aid distribution, and allows residents to quickly report floods. This research focuses on developing a prototype information system at the Jambi City Social Service to handle floods.The steps include initial design, analysis of the existing system, and modeling requirements using UML (Unified Modeling Language). This stage involves creating Use Case, Activity, and Class diagrams, as well as a system prototype.The main goal of this research is to create a system design that can assist in flood reporting, mapping flood-prone areas, and facilitating aid distribution in Jambi City. The result is a prototype system designed to improve the efficiency of flood management in the city.